TTYH1 and TTYH2 Serve as LRRC8A-Independent Volume-Regulated Anion Channels in Cancer Cells - Bae, Yeonju; Kim, Ajung; Cho, Chang-Hoon; Kim, Donggyu; Jung, Hyun-Gug; Kim, Seong-Seop; Yoo, Jiyun; Park, Jae-Yong; Hwang, Eun Mi (MDPI, 2019)
Volume-regulated anion channels (VRACs) are involved in cellular functions such as regulation of cell volume, proliferation, migration, and cell death. Although leucine-rich repeat-containing 8A (LRRC8A) has been characterized as a molecular component of VRACs, here we show that Drosophila melanogaster tweety homologue 1 and 2 (TTYH1 and TTYH2) are critical for VRAC currents in cancer cells. LRRC8A-independent VRAC currents were present in the gastric cancer cell line SNU-601, but almost completely absent in its cisplatin-resistant derivative SNU-601-R10 (R10). The VRAC current in R10 was partially restored by treatment with trichostatin A (TSA), a histone deacetylase inhibitor. Based on microarray expression profiling of these cells, we selected two chloride channels, TTYH1 and TTYH2, as VRAC candidates. VRAC currents were completely absent from TTYH1- and TTYH2-deficient SNU-601 cells, and were clearly restored by expression of TTYH1 or TTYH2. In addition, we examined the expression of TTYH1 or TTYH2 in several cancer cell lines and found that VRAC currents of these cells were abolished by gene silencing of TTYH1 or TTYH2. Taken together, our data clearly show that TTYH1 and TTYH2 can act as LRRC8A-independent VRACs, suggesting novel therapeutic approaches for VRACs in cancer cells.
Keywords: CISPLATIN RESISTANCE; ESSENTIAL COMPONENT; CL-CHANNEL; TWEETY; GENE; EXPRESSION; PROTEIN; FAMILY; LRRC8A; INHIBITOR